Pengaruh Suhu dan Lama Penyimpanan terhadap Stabilitas Minyak Ikan dan Mikrokapsul Minyak Ikan - Montesqrit Montesqrit; R Ovianti (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2013)
Fish oil microcapsules could be stored long longer than fish oil. Storage of the fish oil microcapsules to be more stable and effective to note factors such as temperature and storage time. The purpose of this study was to determine the effect of temperature and storage time on the stability of fish oil (MI) and microencapsulated fish oil (MMI). The research method used was a completely randomized design method factorial 2 x 3 and 3 replications for each MI and MMI. Factor A (storage temperature: refrigerator temperature and room temperature) and factor B (storage time: 15, 30 and 45 days). The variables measured were peroxide, TBA numbers and the total number of oxidation. The results of this study found that the more stable MMI stored in the refrigerator compared to room temperature and the MMI is more stable compared with MI. Temperature and storage time is best for the oxidative stability of microencapsulated fish oil and fish oil are refrigerator temperature and storage time of 45 days.